The impact of social media on consumer behavior (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study analyzes the impact of social media on consumer behavior focusing on the role of influencers, advertisements, and social interaction. The research aims to provide new insights on how companies can use social media as an effective marketing tool.
Keywords: Social Media; Advertising; Consumer Behavior